2014
DOI: 10.1155/2014/138745
|View full text |Cite
|
Sign up to set email alerts
|

The Use of System Codes in Scaling Studies: Relevant Techniques for Qualifying NPP Nodalizations for Particular Scenarios

Abstract: System codes along with necessary nodalizations are valuable tools for thermal hydraulic safety analysis. Qualifying both codes and nodalizations is an essential step prior to their use in any significant study involving code calculations. Since most existing experimental data come from tests performed on the small scale, any qualification process must therefore address scale considerations. This paper describes the methodology developed at the Technical University of Catalonia in order to contribute to the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…In addition, the UPC scaling-up methodology has been checked over two counterpart simulations that were previously qualified with experimental data. The application of the scaling effect and design effect analysis described in [8] has demonstrated that selected phenomena can be perfectly scaled up between counterpart simulations by carefully considering the differences in scale and design. In relation to this, scaled-up and hybrid nodalizations can be used in order to scale results and predict the source of the possible discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the UPC scaling-up methodology has been checked over two counterpart simulations that were previously qualified with experimental data. The application of the scaling effect and design effect analysis described in [8] has demonstrated that selected phenomena can be perfectly scaled up between counterpart simulations by carefully considering the differences in scale and design. In relation to this, scaled-up and hybrid nodalizations can be used in order to scale results and predict the source of the possible discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the PKL and the LSTF experimental facilities, the power-to-volume scaling method was followed for their design. For this criterion, scaling distortions are mainly related to changes in hydraulic diameter, which affects the external heat losses, energy storage in passive structures, friction effects, and flow regime transitions (for more detailed information see the related paper [8]). For analyzing scaling effects of the counterpart test, PVST software (general description in paper [8]) has been applied to the validated UPC PKL pseudo-3D nodalization.…”
Section: Scaling Effect Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the simplicity of the nodalization, the results obtained with this model have shown very good agreement with actual plant data and scaled experimental results. The mentioned model has also been used in several fields of thermal-hydraulic research for the GET group, such as the work performed in the scaling field, see [11] and [12].…”
Section: Introductionmentioning
confidence: 99%